In-orbit Performance of the Near-infrared Spectrograph NIRSpec on the James Webb Space Telescope. (13th March 2023) - Böker, T.; Beck, T. L.; Birkmann, S. M.; Giardino, G.; Keyes, C.; Kumari, N.; Muzerolle, J.; Rawle, T.; Zeidler, P.; Abul-Huda, Y.; de Oliveira, C. Alves; Arribas, S.; et al.
Abstract: The Near-Infrared Spectrograph (NIRSpec) is one of the four focal plane instruments on the James Webb Space Telescope. In this paper, we summarize the in-orbit performance of NIRSpec, as derived from data collected during its commissioning campaign and the first few months of nominal science operations. More specifically, we discuss the performance of some critical hardware components such as the two NIRSpec Hawaii-2RG detectors, wheel mechanisms, and the microshutter array. We also summarize the accuracy of the two target acquisition procedures used to accurately place science targets into the slit apertures, discuss the current status of the spectrophotometric and wavelength calibration of NIRSpec spectra, and provide the "as measured" sensitivity in all NIRSpec science modes. Finally, we point out a few important considerations for the preparation of NIRSpec science programs.